Sustainable nanophytosome-based therapies against multidrug-resistant Escherichia coli in urinary tract infections: an in Vitro and in vivo study - Ming Ming Wen; Ibrahim A. Abdelwahab; Rania Abozahra; Sarah M. Abdelhamid; Kholoud Baraka; Heba Essam Sedky Ahmed; Wessam F. El-Hadidy (Journal of Nanobiotechnology)
Abstract Background Urinary tract infection (UTI) is a prevalent bacterial infection impacting a significant number of individuals globally. The rise in multidrug-resistant (MDR) E. coli strains as the predominant cause of UTIs presents a substantial public health concern and poses a challenge to existing antibiotic treatments. This study introduces an innovative and sustainable therapeutic approach utilizing rosemary oil nanophytosomes as a targeted drug delivery system to address biofilms in UTIs induced by MDR E. coli. Method Seventy clinically identified E. coli isolates from UTI patients were used for this study. Nanophytosomes were formulated with chitosan (CS) and nanostructured lipid carriers. CS-nanophytosomes were lyophilized to evaluate the storage stability. In vivo study included 40 female Wistar rats with daily treatment over seven days. For all the statistical tests, differences were considered significant at p < 0.01 and highly significant at p < 0.001. Results CS-nanophytosomes demonstrated a particle size of 176.70 ± 12.30 nm with a substantial antibiofilm efficacy against MDR E. coli. High entrapment efficiency was ascertained with 93.12 ± 1.05%. The drug release study showed that the pure rosemary oil exhibited a notably lower release of 35.4 ± 2.36% over 48 h. In contrast, the CS-nanophytosomes and lyophilized CS-nanophytosomes displayed significantly higher release percentages of 58.6 ± 3.69% and 56.9 ± 5.01%, respectively, compared to the pure rosemary oil of 35.4 ± 2.36% over 48 h. The in vivo study indicated that nanophytosomes successfully reduced the bacterial load in the urine, bladder, and kidney tissues of mice infected with MDR E. coli, while also lowering the levels of inflammatory cytokines and oxidative stress markers in serum and urine samples. Additionally, the nanophytosomes improved histopathological changes in bladder and kidney tissues caused by UTI without causing any toxicity or adverse effects on kidney function or hematological parameters. Conclusion Our research introduces a cost-effective and innovative approach to addressing UTIs caused by MDR E. coli by the use of rosemary oil, a natural antimicrobial agent encapsulated in nanophytosomes. This strategy not only demonstrates proven therapeutic efficacy in UTI animal models but also promotes the adoption of sustainable medical approaches. CS-nanophytosomes provides a sustainable alternative therapeutic option to combat MDR UTIs. Graphical Abstract